A new species of harlequin frog (Bufonidae: Atelopus) with an unusual behavior from Andes of Colombia - Bravo-Valencia, Laura; Rivera-Correa, Mauricio (Zootaxa, 2011)
A new species of harlequin frog, genus Atelopus, is described from the highlands in the northern part of the Cordillera Central, Colombia. The new species, is distinguished from all other species in the genus by the presence of a postorbital crest widely raised, well defined coni in postocular region and arms, small warts and spiculae scattered on the dorsal surfaces of the body and thighs and, vertebral neural processes conspicuous. Females are uniform dark reddish brown on dorsum, and bright orange ventrally; males are dark brown dorsally, and ventrally white or yellowish with dark brown irregular stripes and blotches. The conservation population status of the new species is discussed, additionally the natural history and aspects about an unusual behavior in the genus is provided.